Late development of Zif268 ocular dominance columus in primary visual cortex of primates - Silveira, Luiz Carlos L (Elsevier, 2019)
Zif268 transcription factor is expressed throughout Cebus apella visual cortex at high basal levels. Monocular eyelid suture alters the levels of Zif268 on neurons connected to the deprived eye, revealing ocular dominance columns in the striate cortex of Cebus as previously demonstrated in Old World monkeys (Chaudhuri and Cynader, Brain Res., 605 (1993) 349?353). Zif268 ocular dominance columns are revealed in adult Cebus monkey after 24?48 h of monocular deprivation, but not in infant monkeys up to 3 months of age. In 6-month-old Cebus monkeys, Zif268 ocular dominance columns are still poorly defined. These results suggest that Zif268 ocular dominance columns establish late during normal primate visual system development, and that some degree of visual plasticity is still present at this age in the Cebus monkey.